Implementasi Pemberian Remisi bagi Narapidana Tindak Pidana Pencurian di Lapas Kelas IIA Rantauprapat: Perspektif Hukum Pidana Islam - Rahma Fitri Amelia Hasibuan; Syaddan Dintara Lubis (CV WAHANA PUBLIKASI, 2026)
The granting of remission is one of the rights of prisoners provided as a form of recognition for behavioral improvement during their incarceration in correctional institutions. This study aims to analyze the implementation of remission for prisoners convicted of theft at the Class IIA Rantauprapat Correctional Institution, identify the factors influencing its implementation, and examine the policy from the perspective of Islamic Criminal Law. This study employs an empirical legal research method with a qualitative approach. Data were obtained through interviews with officers of the Class IIA Rantauprapat Correctional Institution, observations, and documentary studies, and were subsequently analyzed using qualitative descriptive analysis. The findings indicate that the implementation of remission has been carried out in accordance with Law Number 22 of 2022 concerning Corrections and Regulation of the Minister of Law and Human Rights Number 7 of 2022. Supporting factors in the implementation of remission include good prisoner behavior, active participation in correctional programs, fulfillment of administrative requirements, and the use of the Correctional Database System (Sistem Database Pemasyarakatan/SDP). Meanwhile, the main inhibiting factor is disciplinary violations recorded in Register F. From the perspective of Islamic Criminal Law, the granting of remission is consistent with the concept of jarīmah taʿzīr and maqāṣid al-sharīʿah, as it constitutes an authority of the government (ulil amri) aimed at achieving public welfare through rehabilitation, preventing recidivism, and facilitating the social reintegration of prisoners.